Effectiveness of plyometric training vs. complex training on the explosive power of lower limbs: A Systematic review - Wang, Xiaolin; Lv, Changhai; Qin, Xinmin; Ji, Shuyu; Dong, Delong (Frontiers in Physiology, 2023)
Explosive power is considered an important factor in competitive events. Thus, strategies such as complex training (CT) and plyometric training (PLT) are effective at improving explosive power. However, it is still not clear which of the two strategies can enable greater improvements on the explosive power. Thus, the aim of this systematic review was to compare the effects of PLT and CT on the explosive power of the lower limbs. The Review Manager and GraphPad Prism programs were used to analyze the synthetic and time effects (effects over training time) on explosive power (i.e., jump ability, sprint ability) and maximum strength. Our research identified 87 studies comprising 1355 subjects aged 10‒26.4 years. The results suggested the following: 1) Synthetic effects on jump ability (Hedges’ g): 0.79 (P < 0.001) for unloaded PLT, 1.35 (P < 0.001) for loaded PLT and 0.85 (P < 0.001) for CT; 2) Synthetic effects on sprint ability: -0.83 (P < 0.001) for unloaded PLT, -2.11 (P < 0.001) for loaded PLT and -0.78 (P < 0.001) for CT; 3) Synthetic effects on maximum strength: 0.84 (P < 0.001) for loaded PLT and 1.53 (P < 0.001) for CT; 4) The time effects of unloaded PLT and CT on explosive power were similar, but the time effects of CT on maximum strength were obviously above that of PLT. In conclusion, unloaded PLT and CT have a similar effect on explosive performance in the short term but loaded PLT has a better effect. The improvement of the maximum strength caused by CT was greater than that induced by PLT. In addition, more than 10 weeks of training may be more beneficial for the improvement of power. Therefore, for explosive power training, we suggest adopting unloaded or light-loaded PLT during a short season and applying CT during an annual or long training cycle.